A novel magnetic multi-walled carbon nanotube-based magnetic solid-phase extraction combined with dispersive liquid–liquid microextraction method for the determination of four phenoxy carboxylic acid herbicides in food crops by using ultra-high performance liquid chromatography-tandem mass spectrometry. Issue 26 (28th June 2018) - Yuan, Xucan; Liu, Chu; Zhao, Jing; Zhao, Pengfei; Zhao, Longshan
Abstract : A method involving MSPE-DLLME coupled with UHPLC-MS/MS was developed for the determination of four phenoxy carboxylic acid herbicides in food crops. Abstract : A simple, rapid and sensitive method for the determination of four phenoxy carboxylic acid herbicides (4-chlorophenoxy acetic acid, 2-methyl-4-chlorophenoxy acetic acid, 2, 4-dichlorophenoxy acetic acid and 2-(2, 4-dichlorophenoxy)propionic acid) in food crops was established by magnetic multi-walled carbon nanotube assisted magnetic solid-phase extraction combined with dispersive liquid–liquid microextraction followed by ultra-high performance liquid chromatography-tandem mass spectrometry. In our current study, magnetic multi-walled carbon nanotubes were successfully synthesized and characterized by using Fourier transform infrared spectrometry, X-ray diffraction, scanning electron microscopy and vibrating sample magnetometry. The food crops were firstly pretreated with magnetic solid-phase extraction and the extracts were further purified by dispersive liquid–liquid microextraction. Various extraction factors were systematically optimized. Under the optimum conditions, satisfactory sensitivity levels were obtained with the method detection limits of 0.19–0.80 ng g −1 and method quantitation limits of 0.61–2.66 ng g −1 . The recoveries of the four herbicides in different food crops ranged from 83.9 to 102.7% and the precision of the developed method was no more than 10.9%. Furthermore, the method was successfully applied to determine the four phenoxy carboxylic acid herbicides in real food crops (rice, millet, soy, oatmeal, and barley) with satisfactory results.